Novel Synthesis and Characterization of Doxycycline‐Loaded Gold Nanoparticles: The Golden Doxycycline for Antibacterial Applications. (18th December 2018) - Haddada, Maroua Ben; Jeannot, Katy; Spadavecchia, Jolanda
Abstract: Doxycycline (DOXY) is a tetracycline antibiotic with a potent antibacterial activity against a wide variety of bacteria. One potential strategy to enhance the penetration and the antibacterial activity of antibiotics is the use of nanotechnology. In this work, an innovative synthesis of stable PEGylated‐gold nanoparticles (PEG‐AuNPs) loaded with DOXY is reported. As far as it is known, this is the first report on the combination of DOXY with AuNPs as polymeric complex. The obtained nanoparticles are fully characterized by transmission electron microscopy, dynamic light scattering, zeta‐potential, and UV–vis and Raman spectroscopy. The stability and sustained activity of the drug in nanoparticles is determined on a panel of Gram‐positive and Gram‐negative bacteria in comparison with the native form of the drug. This combined therapeutic agent restores the susceptibility of DOXY and shows an antibacterial activity against major human pathogens. Abstract : From synthesis to antibacterial activity . An innovative synthesis of stable PEGylated gold nanoparticles (PEG‐AuNPs) loaded with DOXY is reported. PEG is shown to play a key role in the loading of DOXY around the particle, culminating in an increased bactericidal activity toward major human pathogens.